2010
DOI: 10.1637/9055-090809-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salmonella enterica Serovar Typhimurium Infection on Intestinal Goblet Cells and Villous Morphology in Broiler Chicks

Abstract: Live broiler chickens are important in the transmission of Salmonella to humans. Reducing Salmonella levels in the intestine of broiler chickens, in part, requires understanding of the interactions between Salmonella and the intestinal barriers that represent the first line of defense. Such barriers include the mucus layer (composed of mucins secreted by goblet cells) and the underlying epithelium. Two experiments were conducted to evaluate the effect of Salmonella Typhimurium infection on intestinal goblet ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
35
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 46 publications
12
35
1
2
Order By: Relevance
“…The present results show that the E. coli challenge increased both the number and size of goblet cells in the ileum (Table 4), consistent with an increase in mucin secretion in response to pathogenic bacteria or intestinal microbes that has been previously reported [21,26,27]. Perhaps the increased mucin production is a protective response.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present results show that the E. coli challenge increased both the number and size of goblet cells in the ileum (Table 4), consistent with an increase in mucin secretion in response to pathogenic bacteria or intestinal microbes that has been previously reported [21,26,27]. Perhaps the increased mucin production is a protective response.…”
Section: Resultssupporting
confidence: 91%
“…Measurements included villus height, crypt depth, and the cross-sectional area of sulfo- (stained brown) and sialomucin (stained blue). The measurements for villus height and crypt depth were performed on 10 well-oriented villi [21] scanned at 40× resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we also found that supplemental zinc resulted in increased villus height, villus height to crypt depth ratio and numerically enhanced the activity of sucrase in the ileum after S. typhimurium challenge, which may lead to improved digestive and absorptive function of the gastrointestinal tract. These results are consistent with previous results obtained by ourselves and others (Fasina et al, 2010;Zhang et al, 2012;Shao et al, 2013). The balance between enterocyte proliferation and apoptosis is very important for epithelial cell turnover and intestinal integrity (Yan et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, S. typhimurium infection can result in systemic disease with high mortality in day-old chicks and cause enteric or subclinical disease with reduction of growth performance, intestinal injury and inflammation, and intestinal barrier dysfunction in older birds (Barrow et al, 1987;Barrow et al, 1988;Fasina et al, 2010). Therefore, it is necessary and important to prevent intestinal infection of chickens by Salmonellas to ensure poultry food safety.…”
Section: Introductionmentioning
confidence: 99%
“…59 In addition, increased influx of macrophages and heterophils to the lamina propria and villus epithelium can be observed in chickens infected with enteric pathogens such as Salmonella Typhimurium and Salmonella Enteritidis. 45,60 Although leukocyte infiltration is a defense mechanism against microbial infection during acute inflammatory response, it is worth noting that some pathogens are able to take advantage of this defense mechanism and use it to facilitate its pathogenicity. For instance, Salmonella is known as an intracellular pathogen which is able to survive and replicate in some host cells such as macrophages.…”
Section: Microbiome Affects Intestinal Morphology and Physiologymentioning
confidence: 99%